Knowledge level of Rural Women Regarding Home Science Technologies - Buraka, Kanthisri S; Sreenivasarao, I (Indian Journal of Extension Education, 2020)
Women play a key role in food production and form a large proportion of the agricultural workforce globally. Knowledge empowerment is crucial in women development. Rural women can create wonders in their society with knowledge gain about different Home Science Technologies. A study was conducted in three randomly selected districts of Andhra Pradesh with sample size of 270 Krishi Vigyan Kendra trained respondents with anÂ objective to measure the knowledge level of rural women regarding Home Science Technologies. KnowledgeÂ level was measured in seven different areas â€“ Value addition to millets, nutrition garden, fruit and vegetableÂ preservation, tailoring and embroidery, seed bag technology, vermicompost technology and backyard poultry. The study revealed that average knowledge scores obtained by respondents were medium. The knowledge scores in the areas of fruit and vegetable preservation, value addition to millets. nutrition garden, tailoring andÂ embroidery, vermicompost technology and backyard poultry were in an ascending order. Knowledge scores were significantly related with age, social capital, information source utilisation, innovativeness, value orientation, perception about dissemination method, input availability, market facility and institutional support. The degree of contribution and influence exerted by the different precursor variables than studied variables was observed. Further studies to explore other correlated factors are needed.